Parental responses and catastrophizing in online cognitive behavioral therapy for pediatric functional abdominal pain: A mediation analysis of a randomized controlled trial - Lalouni, Maria; Bujacz, Aleksandra; Bonnert, Marianne; Jensen, Karin B.; Rosengren, Anna; Hedman-Lagerlöf, Erik; Serlachius, Eva; Olén, Ola; Ljótsson, Brjánn (Frontiers in Pain Research, 2022)
Objective To test if decreased parental protective behaviors, monitoring behaviors, and parental catastrophizing mediate relief of gastrointestinal symptoms in children 8–12 years with functional abdominal pain disorders (FAPDs). The study uses secondary data analyses of a randomized controlled trial in which exposure-based online cognitive behavioral therapy (ICBT) was found superior to treatment as usual in decreasing gastrointestinal symptoms. Methods The ICBT included 10 weekly modules for children and 10 weekly modules for parents. Treatment as usual consisted of any medication, dietary adjustments, and healthcare visits that the participants engaged in during 10 weeks. All measures were self-assessed online by parents. Biweekly assessments of the Adult Responses to Children's Symptoms (ARCS), Protect and Monitor subscales, and the Pain Catastrophizing Scale, parental version (PCS-P) were included in univariate and multivariate growth models to test their mediating effect on the child's gastrointestinal symptoms assessed with the Pediatric Quality of Life Gastrointestinal Symptoms Scale (PedsQL). Results A total of 90 dyads of children with FAPDs and their parents were included in the study, of which 46 were randomized to ICBT and 44 to treatment as usual. The PCS-P was found to mediate change in the PedsQL ab = 0.639 (95% CI 0.020–2.331), while the ARCS Monitor ab = 0.472 (95% CI −1.002 to 2.547), and Protect ab = −0.151 (95% CI −1.455 to 0.674) were not mediators of change. Conclusions To target parental catastrophizing in ICBT for pediatric FAPDs is potentially important to reduce abdominal symptoms in children.